2020
DOI: 10.3390/ijerph17197231
|View full text |Cite
|
Sign up to set email alerts
|

The Devil Is in the Detail: Challenging the UK Government’s 2019 Impact Assessment of the Extent of Online Marketing of Unhealthy Foods to Children

Abstract: Background: How much unhealthy marketing do children see on digital devices? Marketing of unhealthy food and beverages has long been identified as a factor in children’s preferences, purchase requests and consumption. Rising global obesity mandates States to craft environments that protect children and young people’s health, as recommended by the World Health Organization, among others. However, assessing the impact of marketing restrictions is particularly challenging: the complexity of digital advertising ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…Targeted marketing of SSB and other unhealthy foods to people of color and low socioeconomic status takes advantage of their more limited options for healthy food choices and their need for product affordability, while ignoring their greater risk for obesity and obesity-related diseases. Therefore, in response to question 4, we echo others [ 120 ••, 121 , 122 ••, 123 127 , 128 ••, 129 , 130 • 131 133 , 134 ••, 135 , 136 •, 137 – 149 , 150 •, 151 153 , 155 ••] in suggesting that proactive environmental measures to decrease exposure to palatable food cues, particularly in the form of targeted marketing to our vulnerable populations, is a necessary strategy for slowing the obesity epidemic.…”
Section: Resultssupporting
confidence: 51%
See 1 more Smart Citation
“…Targeted marketing of SSB and other unhealthy foods to people of color and low socioeconomic status takes advantage of their more limited options for healthy food choices and their need for product affordability, while ignoring their greater risk for obesity and obesity-related diseases. Therefore, in response to question 4, we echo others [ 120 ••, 121 , 122 ••, 123 127 , 128 ••, 129 , 130 • 131 133 , 134 ••, 135 , 136 •, 137 – 149 , 150 •, 151 153 , 155 ••] in suggesting that proactive environmental measures to decrease exposure to palatable food cues, particularly in the form of targeted marketing to our vulnerable populations, is a necessary strategy for slowing the obesity epidemic.…”
Section: Resultssupporting
confidence: 51%
“…In the USA, there are no statutory regulations that limit the marketing of unhealthy foods to children [ 123 ]. The obstacles to such regulations include the economic power of the industry [ 124 – 126 ], prioritizing individual rights over public health outcomes [ 127 ], and the challenges of regulating advertising through digital media, which was recently described as the most significant paid-for media channel for unhealthy advertising to children [ 128 ••]. In 2019, the California Dental Association and the California Medical Association launched a campaign to highlight the soda industry’s marketing strategies targeted at children and low-income and minority communities [ 129 ].…”
Section: Introductionmentioning
confidence: 99%
“…The number of advertising impressions (views by children) that were estimated using this approach was approximately five times greater for television advertising than for web-based marketing. Interrogations of the approach used by academics suggested that the impact assessment underestimated children’s actual web-based food marketing exposures by 10-fold [ 41 ]. This study supports this finding, whereby Australian children’s web-based food marketing exposures are approximately nine times higher than their exposure to food advertising on television.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are obstacles in the process of implementing government intervention. As a result of these obstacles, in many cases, government intervention does not achieve the expected goal [ 40 , 41 ]. This study finds that government intervention in China is negatively associated with food safety performance, which is contrary to the research conclusions of Lv et al, Wang et al, and Duan et al, all of which find that government intervention has a positive influence on other industries [ 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%